1993
DOI: 10.1111/j.1471-4159.1993.tb02146.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Alterations in Purine Nucleotide Metabolism in Hypoxanthine‐Guardne Phosphoribosyltransferase‐Deficient Rat Neuroma Cell Line

Abstract: A rat neuroma cell line (B103 4C), deficient of hypoxanthine‐guanine phosphoribosyltransferase (HGPRT), was utilized as a model tissue in search for the biochemical basis of the Lesch‐Nyhan syndrome (LNS). The HGPRT‐deficient neurons exhibited the following properties: an almost complete absence of uptake of guanine and of hypoxanthine into intact cell nucleotides (0.92% and 0.69% of normal, respectively); a significant increase in the availability of 5′‐phosphoribosyl‐1‐pyrophosphate; a three‐ to fourfold acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
24
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 37 publications
7
24
0
Order By: Relevance
“…Major advantages of B103 cells are that they are well characterized and broadly used in the neurosciences since the 1970s until now for topics encompassing addiction, cellular ultrastructure, differentiation, tumor cell biology, neurodegeneration, neurotoxicity, receptor function, and signal transduction, and that they grow rapidly and reproducibly (Schubert et al 1974;Cabral et al 1987;Kokoz et al 1999;Kawanabe et al 2001;Han et al 2002;Tanura et al 2006;Crespo-López et al 2007;Han et al 2010;Kato et al 2012). A HPRT-deficient clone of B103 cells was generated by selection of 6-thioguanine-resistant cells (Zoref-Shani et al 1993). In HPRT-deficient cells, 6-thioguanine cannot be converted to the cytotoxic 6-thioguanosine 5′-triphosphate and hence, cells survive (Zoref-Shani et al 1993;Hacke et al 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Major advantages of B103 cells are that they are well characterized and broadly used in the neurosciences since the 1970s until now for topics encompassing addiction, cellular ultrastructure, differentiation, tumor cell biology, neurodegeneration, neurotoxicity, receptor function, and signal transduction, and that they grow rapidly and reproducibly (Schubert et al 1974;Cabral et al 1987;Kokoz et al 1999;Kawanabe et al 2001;Han et al 2002;Tanura et al 2006;Crespo-López et al 2007;Han et al 2010;Kato et al 2012). A HPRT-deficient clone of B103 cells was generated by selection of 6-thioguanine-resistant cells (Zoref-Shani et al 1993). In HPRT-deficient cells, 6-thioguanine cannot be converted to the cytotoxic 6-thioguanosine 5′-triphosphate and hence, cells survive (Zoref-Shani et al 1993;Hacke et al 2012).…”
mentioning
confidence: 99%
“…A HPRT-deficient clone of B103 cells was generated by selection of 6-thioguanine-resistant cells (Zoref-Shani et al 1993). In HPRT-deficient cells, 6-thioguanine cannot be converted to the cytotoxic 6-thioguanosine 5′-triphosphate and hence, cells survive (Zoref-Shani et al 1993;Hacke et al 2012). HPRTdeficient B103 cells are an established cell culture model for LND and have already been used for two decades to study various aspects of the pathophysiology of LND including alterations in neuronal differentiation, nucleotide metabolism, purinoceptor function, nucleotidase activity, nucleotidase gene expression, and adenylyl cyclase (AC) regulation (Zoref-Shani et al 1993;Ma et al 2001;Connolly 2001;Pinto et al 2005;Pinto and Seifert 2006;Lorenz et al 2007;Erdorf et al 2011a).…”
mentioning
confidence: 99%
“…These abnormalities include decreases in the intracellular concentrations of the purine nucleotide GTP and increased concentration of ATP (Fairbanks et al . 2002) and, in some instances, compensatory increases in the intracellular concentrations of the pyrimidine nucleotides UTP and CTP (Zoref‐Shani et al . 1993; Pelled et al .…”
mentioning
confidence: 99%
“…Similar to LND patients, there are abnormalities in dopaminergic neurotransmission in the HPRT knock-out mouse [7,16]. In addition, several HPRT-deficient cell lines including primary human skin fibroblasts, immortalized mouse skin fibroblasts, mouse Neuro2a neuroblastoma cells and rat B103 neuroblastoma are used as biochemical models for LND [18,2,4,12,11]. In a recent study [11] we showed that nucleoside 5 -triphosphatase (NTPase) activity in B103-and Neuro2a cell membranes is reduced in HPRT-deficiency.…”
mentioning
confidence: 99%
“…Given the well-known species-specificity of biochemical changes in HPRT-deficiency [18,2,4,12,11], one has to be cautious with extrapolations to LND. Accordingly, in future studies, human neuronal cell culture cell lines will have to be studied.…”
mentioning
confidence: 99%